Early detections of SARS-CoV-2 in wastewater and their use in COVID-19 epidemiological control - Mainardi, Pedro Henrique [UNESP]; Bidoia, Ederio Dino [UNESP] (Universidade Federal de Itajubá, 2021)
SARS-CoV-2 is a new type of coronavirus that is capable to infect humans and cause the severe acute respiratory syndrome COVID-19, a disease that has been causing enormous impacts across the whole Earth. COVID-19 patients, including mild, pre-symptomatic and asymptomatic cases, were often seen to contain infectious fragments of SARS-CoV-2 in urine and feces samples. Thus, studies to detect the new coronavirus in wastewater, which collect and concentrate human excreta, have been extremely useful as a tool to monitor the virus spread in the communities. The surveillance, frequently used to elaborate economical non-invasive diagnoses about the circulation of chemicals and pollutants in populations, could be used as a quick alert about emerging and reemerging COVID-19 epidemics, improve the predictions concerning the SARS-CoV-2 dissemination and promote the development of better viral containment measures. Along that, the approach could be used to construct more accurately epidemiological models, foment better practices to coordinate resources an administer the vaccines, assess the propagation of SARS-CoV-2 variants across temporal and geographic scales, evaluate environmental risks and also the effectiveness of disinfection systems. In this review, it was addressed early reports regarding SARS-CoV-2 detections in wastewater and the importance of this valuable approach in the application of faster and more effective interventions from public health authorities, either towards the COVID-19 or any other epidemic disease in the future.

O SARS-CoV-2 é um novo tipo de coronavírus capaz de infectar humanos e causar a síndrome respiratória aguda grave COVID-19, doença que vem causando enormes impactos em todo o planeta Terra. Pacientes com COVID-19, incluindo casos leves, pré-sintomáticos e assintomáticos, frequentemente foram vistos por conter em amostras de urina e fezes fragmentos infecciosos do SARS-CoV-2. Sendo assim, estudos para detectar o novo coronavírus em águas residuárias, que coletam e concentram os excrementos humanos, têm sido extremamente úteis como uma ferramenta para monitorar a disseminação do vírus nas comunidades. A vigilância, frequentemente utilizada para elaborar diagnósticos econômicos e não invasivos sobre a circulação de produtos químicos e poluentes nas populações, poderia ser utilizada como um alerta rápido sobre epidemias emergentes e reemergentes de COVID-19, melhorar as previsões acerca da propagação do SARS-CoV-2 e promover o desenvolvimento de melhores medidas de contenção viral. Além disso, a abordagem poderia ser utilizada para construir modelos epidemiológicos com maior precisão, fomentar melhores práticas para coordenar recursos e administrar as vacinas, avaliar a propagação de variantes do SARS-CoV-2 em escalas temporais e geográficas, avaliar riscos ambientais e também a eficácia dos sistemas de desinfecção. Nesta revisão, foram abordados os relatos precoces de detecção do SARS-CoV-2 em águas residuais e a importância dessa valiosa abordagem na aplicação de intervenções mais rápidas e eficazes por parte das autoridades de saúde pública, seja em relação à COVID-19 ou qualquer outra doença epidêmica no futuro.
La detección precoz de SARS-CoV-2 en las aguas residuales y su uso en el control epidemiológico de COVID-19
Detecções precoces do SARS-CoV-2 em águas residuais e seu uso no controle epidemiológico do COVID-19
Keywords: Epidemiologia; Água - Reuso; Saúde pública; Medicina preventiva; Vigilância epidemiológica; Síndrome respiratória aguda grave